On the mean value of the function $\overline{S}_k(n)$ - Varbanets, P. D.; Kirbat, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
An asymptotic formula is constructed for a mean value of the function $\overline{S}_k(n)$ which is dual to the Smarandache function $S_k(n)$. $O$- and $Ω$-estimates for the second moment of the remainder term are obtained.